Development and Validation of a Stability-Indicating High Performance Thin Layer Chromatography (HPTLC) Method for estimation of Canagliflozin in bulk and Pharmaceutical Dosage Form - Ishpreet Kaur, Sharad Wakode, Harsharan Pal Singh (Journal of Applied Pharmaceutical Science, 2016)
The objective of the study was to develop and validate simple, authentic and stability indicating high performance thin-layer chromatographic method for determination of Canagliflozin in bulk and pharmaceutical formulations as per ICHQ2 R1 Guidelines. HPTLC aluminium plates Precoated with Silica Gel 60F254 using Toluene: Ethyl acetate: Methanol (2:2:1, v/v/v) as mobile phase were used for the chromatographic separation and it was validated with different parameters such as Linearity, Precision, Accuracy, Robustness, Ruggedness, Limit of Detection (LOD) and Limit of Quantification (LOQ). Also, Forced degradation study was carried out in different mediums. The densitometric analysis of the spots was performed at 290 nm. A Linear data over the range of 10-500ng/spot with a good correlation coefficient of 0.9988 unfolds linear relationship between area and concentration in calibration curve. The LOD and LOQ were found to be 0.39 and 1.19 respectively. A recovery of Canagliflozin in tablet formulation was observed in the range of 99.04-99.82%. Percentage assay of Canagliflozin tablets (INVOKANA®) was found to be 99.8%. Forced degradation studies of canagliflozin showed the degradation in acidic, alkaline, photolytic and oxidation but were most stable in thermal degradation. The proposed method is definite, meticulous and reproducible and can be used for routine analysis of Canagliflozin in bulk and pharmaceutical dosage form.
Keywords: Canagliflozin, Chromatographic separation, Forced Degradation, Method development, Validation.